Safety of 0.1% topical tacrolimus in the treatment of vitiligo (Bangladesh Journal of Medical Science, 2014)
Cure rates for vitiligo are significantly lower because of problems to different studies have reported different response rate and different adverse effect for the treatment of vitiligo. This study was conducted to evaluate the response rate and adverse effect of topical tacrolimus 0.1% ointment in the treatment of vitiligo patients in the department of Dermatology and venereology, Bangladesh Medical college (BMC), Dhaka from January 2010 to July 2010. In this clinical trial, 30 newly diagnosed vitiligo (focal and segmental) patients, aged between 10 to 50 years were assigned for therapy and to observe the response and adverse effect. Each individual lesion was treated with topical tacrolimus 0.1% ointment twice daily for three months. All the patients completed three months treatment and available for statistical analysis. The highest percentage 13(43.3%) was in the age of 11-20 years. Sex ratio revealed higher in case of female 18(60%), with a male-female ratio 1:1.5 and 5(16.67%) patients had vitiligo among their families. Repigmentation was observed in 8 (26.7%) subjects at the end of 4th week, 15 (50.1%) subjects at 8th week and 25 (83.3%) subjects after 12 weeks of therapy. 25 (83.33%) subjects did not complain any adverse effect (like pruritus, burning etc.) and 5 (16.67%) subjects were suffered from different adverse effect of drug, like pruritus observed in 2 (6.7%) subjects and burning in 6 (20%) subjects. This study found that tacrolimus 0.1% ointment to be safe in the treatment of vitiligo, with reduction in the number of vitiliginous spots by increased repigmentation significantly. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19147 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.255-259